2015
DOI: 10.5152/tao.2015.1178
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Sentinel Lymph Node Biopsy in Oral Cavity Cancers

Abstract: Objective: The aim of this study was to establish the effectiveness of sentinel lymph node biopsy in the detection of metastasis in N0 necks of T1-T2 early-stage oral cavity cancers. Materials and Methods:Twenty neck dissections were performed in 18 patients diagnosed with T1 and T2 oral cavity cancer, with an indication for elective neck dissection between November 2007 and January 2011. The male to female ratio was 12:8, with a mean age of 54.5 years (range 28-76). Eight of the dissections were performed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Two authors individually collected data from included articles in forms commensurate with each other. Diagnostic accuracy, represented by DOR, summary receiver operating characteristic (SROC) curve, and area under the curve (AUC), was calculated 1,5,11–102 . DOR was calculated as (true positive [TP]/false positive [FP])/(false negative [FN]/true negative [TN]) to assess diagnostic accuracy with 95% confidence intervals (CIs).…”
Section: Methodsmentioning
confidence: 99%
“…Two authors individually collected data from included articles in forms commensurate with each other. Diagnostic accuracy, represented by DOR, summary receiver operating characteristic (SROC) curve, and area under the curve (AUC), was calculated 1,5,11–102 . DOR was calculated as (true positive [TP]/false positive [FP])/(false negative [FN]/true negative [TN]) to assess diagnostic accuracy with 95% confidence intervals (CIs).…”
Section: Methodsmentioning
confidence: 99%
“…Kaya et al found, after the final SLN histopathological examination, that the negative predictive value, the positive predictive value, the accuracy of SLN biopsy ,and the accuracy of the frozen sections were equal to 100%. It should be noted that the study group consisted of 18 patients [29]. A limitation of the method arises when the tumor and SLN are in close proximity.…”
Section: Mapping With a Radioactive Substancementioning
confidence: 99%